Blasting, effect of weather conditions : noise pollution : pollution noise, blasting. (U.S. Department of the Interior, Bureau of Land Management, Portland Service Center, 1971)
Announces an article printed in 73 Rock Products 6 (June 1970) titled, 'Weather Condition Checks Aid Public Relations at Granite Quarry' written by James J. Shannon. The article discusses noise pollution caused by mine blasting and potential aggravated effects due to weather conditions.
"Filing code: 3040."
"Mailing list 1."
Keywords: Mineral industries -- Environmental aspects -- United States.; Blasting -- Environmental aspects -- United States.; Noise pollution -- United States.; Noise pollution -- Meteorological aspects -- United States.; Blasting -- Environmental aspects.; Mineral industries -- Environmental aspects.; Noise pollution.; Noise pollution -- Meteorological aspects.; United States.